Brachytherapy in Men with Prostate Cancer: Update on Indications and Outcomes. Issue 2 (April 2013) - Pinto, Francesco; Calarco, Alessandro; Recupero, Salvatore Marco; Totaro, Angelo; Sacco, Emilio; Bassi, PierFrancesco
Brachytherapy (BT), using either a low-dose-rate (LDR) or mostly high-dose-rate (HDR) technique, is the device able to deliver the highest dose-rate in the most conformal way It is used as monotherapy or in combination with external beam radiotherapy (EBRT). LDR-BT is mostly used as monotherapy; HDR-BT is combined with EBRT +/– adjuvant hormone therapy In patients with low-risk disease and in selected intermediate-risk patients, LDR-BT ensures long-term good disease control rates and HDR-BT shows similar results, even if with shorter follow-up. In patients with intermediate/high risk disease the combination therapy (EBRT + HDR-BT) provides better oncological outcomes compared to EBRT monotherapy, even if the role of adjuvant hormone therapy is still unclear. Literature shows variable efficacy of BT in case of local recurrence after EBRT and radical prostatectomy even if few cases have been reported with short follow-up. Side effects are acceptable (urogenital toxicity, urinary incontinence, sexual function) and comparable with the other treatment modalities. So far, randomized controlled trials comparing the different treatment modalities are necessary to clarify indications and real efficacy.